Cementation behavior of gold and silver onto Zn, Al, and Fe powders from acid thiourea solutions - Lee, HY; Kim, SG; Oh, JK (MANEY PUBLISHING, 1997)
Research on the cementation behavior of gold and silver from acid thiourea solutions was carried out with zinc, aluminum, and iron powders and discussed in view of industrial application. An acid thiourea pregnant solution, containing 96 mg/dm(3) gold and 534 mg/dm(3) silver was used during this investigation. The effect of gas atmosphere on cementation of precious metals was also examined by flowing nitrogen gas through the solution during the runs. According to the results, zinc cementation showed the highest rate of deposition of precious metals from acid thiourea solutions. The deposition of silver was slower than that of gold in every cementation tested. The low deposition of precious metals in aluminium cementation at low temperature was due to the oxide film on the surface of aluminum, which caused the irregularly slow rate of deposition. In addition, it was observed that the recovery of precious metals was enhanced, and that both the decomposition of thio urea and the metal dissolution were reduced considerably by employing a nitrogen atmosphere during cementation. Published by Elsevier Science Ltd.